Association between type of exercise and health-related quality of life in adults without activity limitations: a nationwide cross-sectional study - Min-Jung Choi; Yong Gyu Park; Yang Hyun Kim; Kyung Hwan Cho; Ga Eun Nam (BMC Public Health, 2020)
Abstract Background Exercise is known to be associated with health-related quality of life (HRQoL), however, evidence on the association between type of exercise and HRQoL in the general population is limited. We performed this study to investigate the association of exercise types and their combinations with HRQoL in Korean adults. Methods We analyzed data from 13,437 adults aged ≥19 years without activity limitations who had participated in the 5th Korea National Health and Nutrition Examination Survey 2010–2012. As per the American College of Sports Medicine guideline, exercise types were categorized into eight groups: walking (W), flexibility (F), resistance (R), W + F, W + R, F + R, and W + F + R exercise groups and a non-exercise group. The European Quality of Life-5 Dimension (EQ-5D) index and the European Quality of Life Visual Analogue Scale (EQ-VAS) were used to assess HRQoL. Results The mean age of participants was 42.8 ± 0.2 years. The proportion of participants in the non-exercise group was the highest (34.7%); among the exercise groups, the walking group was the most prevalent (16.9%) and the W + R group was the least (1.2%). In analysis of covariance, the mean EQ-5D index in W (0.875), W + F (0.878), F + R (0.877), and W + F + R (0.876) groups was significantly higher compared with that in non-exerciser group (0.869) (p < 0.05). The mean EQ-VAS score in the W (64.064), F (64.427), W + F (65.676), F + R (65.811), and W + F + R (67.110) groups was higher than that in the non-exercise group (62.396) (p < 0.05). No difference was observed between R and W + R groups and non-exercise group with regard to the EQ-5D index and EQ-VAS score. Conclusions The W (for 30 min at least five times a week), W + F, F + R (at least two days a week), and W + F + R groups showed higher HRQoL than the non-exercise group. This study may be helpful in the development of public exercise interventions, which could help enhance HRQoL in adults.